10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Youth participatory action research (YPAR) elevates youth as change agents in their schools and communities. The YPAR studies have demonstrated impact on psychological empowerment and civic engagement, both thought to lead to improved health. This exploratory evaluation assessed physical and emotional health among youth in a YPAR program. We implemented an eight-session YPAR program across four neighborhoods in Pittsburgh, PA. Surveys were administered at baseline, end-of-program (EOP), and 1 year from baseline (T3) to measure changes in the following: psychological empowerment, civic engagement, emotional health, health care access and quality of life, and substance use. Descriptive statistics were used to summarize variables at each timepoint. Generalized linear mixed models assessed changes in outcomes over time, with results presented as odds ratios (ORs) or parameter estimates (β) with 95% confidence intervals. Seventy-one youth completed baseline surveys, 58 completed EOP surveys, and 43 completed T3 surveys. Most youth identified as non-Hispanic Black. Compared to baseline, youth at EOP and T3 reported consistently higher levels of psychological empowerment (EOP: β = 0.39 [0.22-0.56]; T3: β = 0.36 [0.17-0.55]) and civic engagement (EOP: β = 0.34 [0.15-0.54]; T3: β = 0.34 [0.12-0.56]). Youth reported greater difficulties in emotion regulation (β = 0.26 [0.07-0.45]) and fewer activity limitations (OR = 0.31 [0.12-0.77]) at EOP, but findings did not persist at T3. There were no changes in measures of health care access or substance use. The YPAR is consistently associated with increases in psychological empowerment and civic engagement. Findings suggest opportunities to integrate health-related resources in YPAR programming and to assess health impacts of such interventions.